Gadget overload: Ancaman diam di era digital - Nazilah, Nishfi Rohmatun (Maliki Interdisciplinary Journal, 2025)
In the rapidly evolving digital era, the use of gadgets has become an integral part of everyday life, whether for children, teenagers or adults. However, despite its convenience and benefits, the phenomenon of gadget overload has posed serious threats to mental, physical and social health. This article aims to examine the negative impacts of gadget overuse, including addiction, mental health disorders such as anxiety and depression, and disruptions in family and community relationships. Based on a literature review, this article identifies factors that cause gadget overload, such as lack of parental supervision, social pressure, and dependence on technology. In addition, it explores mitigation strategies, such as digital safety education, screen time management, and wise parenting approaches in the digital age. Utilizing references from various academic sources, this article offers in-depth insights on how society can balance the use of technology to prevent the adverse effects of gadget overload.